Inhibition of Podocytes DPP4 Activity Is a Potential Mechanism of Lobeliae Chinensis Herba in Treating Diabetic Kidney Disease - Wang, Xinyu; Xiang, Jiaqing; Huang, Guixiao; Kang, Lin; Yang, Guangyan; Wu, Han; Jiang, Kewei; Liang, Zhen; Yang, Shu (Frontiers in Pharmacology, 2021)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease and has become a serious public health problem worldwide. Dipeptidyl peptidase-4 (DPP4) inhibitors, an emerging drug for the treatment of diabetes, have been found to have renoprotective effects in addition to glucose-lowering effects and therefore have the potential to be a treatment modality for DKD. Lobeliae Chinensis Herba (LCH), a traditional Chinese herb widely used in the treatment of diabetes, has recently been found to have a hypoglycaemic mechanism related to the inhibition of DPP4. Firstly, analysis of single-cell sequencing data from mouse kidneys in the National Center for Biotechnology Information (NCBI) database revealed that DPP4 was specifically upregulated in DKD podocytes and was associated with podocyte proliferation. Subsequently, the network pharmacology approach was applied to the screening of compounds. Twelve LCH active ingredients targeting DPP4 were extracted from the Traditional Chinese Medicine System Pharmacology (TCMSP) database. In addition, these 12 compounds and DPP4 were molecularly docked to predict the probability of them affecting DPP4 activity. In vitro, Quercetin, Methyl rosmarinate, Kaempferol, Diosmetin and Acacetin were demonstrated to retard podocyte proliferation by inhibiting DPP4 activity and were the top five compounds predicted by molecular docking to be the most likely to affect DPP4 activity. The half maximal inhibitory concentration (IC50) of the five compounds for DPP4 activity were as follows. Acacetin Log IC50 = −8.349, 95%CI (−9.266, −7.265), Diosmtrin Log IC50 = −8.419, 95%CI (−8.889, −7.950), Log IC50 = −8.349, 95%CI (−9.266, −7.265), Methyl rosmarinate Log IC50 = −8.415, 95%CI (−8.751, −8.085), Kaempferol Log IC50 = −8.297, 95%CI (−9.001, −7.615), Quercetin Log IC50 = −8.864, 95%CI (−9.107, −8.615). Finally, Quercetin, Methyl rosmarinate, Kaempferol, Diosmetin and Acacetin qualified for pharmacokinetic and drug similarity screening and have the potential to be the most promising oral agents for the treatment of DKD.